Occurrence and Characterization of NDM-1-Producing Shewanella spp. and Acinetobacter portensis Co-Harboring tet(X3) in a Chinese Dairy Farm - Ruichao Li; Lifei Zhang; Xiaoyu Lu; Kai Peng; Yuan Liu; Xia Xiao; Hongqin Song; Zhiqiang Wang (MDPI AG, 2022)
Bacteria with carbapenem or tigecycline resistance have been spreading widely among humans, animals and the environment globally, being great threats to public health. However, bacteria co-carrying drug resistance genes of carbapenem and tigecycline in Shewanella and Acinetobacter species remain to be investigated. Here, we detected nine blaNDM-1-carrying Shewanella spp. isolates as well as three A. portensis isolates co-harboring tet(X3) and blaNDM-1 from seventy-two samples collected from a dairy farm in China. To explore their genomic characteristic and transmission mechanism, we utilized various methods, including PCR, antimicrobial susceptibility testing, conjugation experiment, whole-genome sequencing, circular intermediate identification and bioinformatics analysis. Clonal dissemination was found among three A. portensis, of which tet(X3) and blaNDM-1 were located on a novel non-conjugative plasmid pJNE5-X3_NDM-1 (333,311 bp), and the circular intermediate ΔISCR2-tet(X3)-blaNDM-1 was identified. Moreover, there was another copy of tet(X3) on the chromosome of A. portensis. It was verified that blaNDM-1 could be transferred to Escherichia coli C600 from Shewanella spp. by conjugation, and self-transmissible IncA/C2 plasmids mediated the transmission of blaNDM-1 in Shewanella spp. strains. Stringent surveillance was warranted to curb the transmission of such vital resistance genes.